Elementos estéticos e relações simbólicas no ritual do Reis de Boi - Zimerer, Fabiane Vasconcelos Salume (2017)
Reis de Boi is a cultural practice from two cities, São Mateus and Conceição da Barra, located at the north of the state of Espírito Santo. It is related to the Christmas cycle and celebrates the Three Kings. The celebration starts on the 6th of January (